The Effect Of JKP On The Percentage of NEET In Indonesia - Teger Ivo Bangun; Dwini Handayani (Eduvest - Journal of Universal Studies, 2024)
The NEET rate in Indonesia is the highest among other ASEAN countries and has increased in 2022, coinciding with the first year JKP benefits can be claimed. The purpose of this study is to see and analyze the effect of JKP on the percentage of NEET in Indonesia. Using August 2022 sakernas data and 2021 podes data in the form of cross-section data, this study was conducted using the Ordinary Least Square method. The analysis used in this research is descriptive analysis and inferential analysis in the form of regression analysis. The results of the analysis show that a 1% increase in the number of youth JKP recipients in the district/city reduces the percentage of NEET youth by 0.62% in 2022. Suggestions for the government are to increase JKP participation among youth aged 15-24 years. Review the requirements, claim procedures and obligations of JKP beneficiaries, to mitigate the risk of moral hazard.